Strategi Komunikasi Pemasaran Café Embun Senja Semarang dalam Meningkatkan Penjualan - Muhammad Bahrul Alam Alfuady; Fikri Shofin Mubarok (CARONG: Jurnal Pendidikan, Sosial dan Humaniora, 2025)
This study analyzes the marketing communication strategies implemented by Café Embun Senja in Semarang, focusing on sales enhancement. Using a qualitative approach, data were collected through interviews with the manager and staff, as well as direct observations. The findings reveal that social media, particularly Instagram, plays a crucial role in promoting products and building customer relationships. Additionally, promotional strategies such as discounts, special events, and engaging content significantly contribute to increased visitors and sales. Personal selling also enhances the customer experience, encouraging repeat visits. Overall, the combination of various marketing communication elements, including advertising, public relations, and direct marketing, has a positive impact on customer loyalty. This study offers insights for the management of Café Embun Senja to further develop more effective marketing communication strategies.